About the History of philosophy by Tadeusz Gadacz - Woleński, Jan (Diametros, 2010)
Review of the book: Tadeusz Gadacz, Historia filozofii XX wieku. Nurty, Tom II: Neokantyzm. Filozofia egzystencji. Filozofia dialogu, Wydawnictwo Znak, Kraków 2009